PERAN AKUNTAN DALAM IMPLEMENTASI GOOD CORPORATE GOVERNANCE (GCG) DI INDONESIA - Lilis Saidah Napisah (LPPM POLITEKNIK LP3I BANDUNG, 2015)
Under ethics-based and regulatory-based approaches, the implementation of good corporate governance (GCG) is intended to improve value added for stakeholders and to encourage fair competition and conducive business climate leading to sustainable economic growth and stability. Good Corporate Governance which includes general principles such as transparancy, accountability, responsibility, independency, and fairness is necessary to attain a company’s sustainability by considering the interests of stakeholders. In implementation of GCG, accountants have significant roles to provide material, timely, appropriate, clear, accurate, comparable, relevan, accessible information to stakeholders and also disclose it. In addition, accountants (internal auditors) must ensure the existence of an effective internal control system within a company. Financial accountants, management accountants, internal auditor, external auditors and audit committees have strategic positions in implementation of good corporate governance in Indonesia.